Opioid-Related Incident Severity and Emergency Medical Service Naloxone Administration by Sex in Massachusetts, 2013–2019. Issue 1 (December 2022) - Bettano, Amy; Jones, Katarina; Fillo, Katherine T.; Ficks, Ridgely; Bernson, Dana
Background : A Cross-sectional study of all emergency ambulance runs reported by licensed Emergency Medical Services (EMS) providers between 2013 and 2019 was undertaken to determine if the sex of a patient experiencing opioid-related symptoms had an impact on their odds of receiving naloxone from EMS. Methods: All runs within Massachusetts for individuals 11 years and older with a reported sex between 2013 and 2019 ( n  = 5, 533, 704 runs) were included. Covariates modeled were patient age, year of the incident, and county of the incident. Runs were separated into those that were opioid-related versus not; opioid-related runs were further subdivided into five severity categories including dead on arrival, acute opioid overdose, opioid intoxicated, opioid withdrawal, and other opioid-related incident. Results: Among opioid-related runs, women had 24% lower odds (95% CI 0.68–0.86) of appearing in the dead on arrival category and 20% lower odds (95% CI 0.78–0.82) of appearing in the acute opioid overdose category than men. Among acute opioid overdoses, runs where patient symptoms met Massachusetts EMS guidelines for naloxone administration, women had 18% lower odds (95% CI 0.76–0.89) of receiving naloxone than men. Conclusions: Sex-related differences persist in the odds of naloxone administration by EMS providers when controlling for symptom presentation.